Seasonal and annual crop evapotranspiration in Europe over 2011–2070 - Nistor, Margarit Mircea (2019)
The knowledge of evapotranspiration variation is necessary not only for climatology reasons but also for agriculture and hydrology purposes to understand the amount of water resources and its distribution in territory. Here, we present an exhaustive study of spatial distribution of crop evapotranspiration (ETc) in Europe, both for seasonal and annual time-shifts related to the present (2011–2040) and the future (2041–2070). The method is based on the crop coefficients (Kc) and the climate modes. The seasonal ETc varies in Europe from 0 mm to 772 mm in the present period and from 0 mm to 848 mm in the future period. The annual ETc ranges from 0 mm to 1385 mm year-1 for the present while the future calculations indicate values which range from 0 mm to 1496 mm year-1. Elevated values of annual ETc were depicted in the Iberian Peninsula, Balkan Peninsula, Italian Peninsula, and Pannonian basin. These findings are the base for the water resources quantity in Europe for the 21st century, with major help in the hydrological and climatological studies, but also for the agriculture and planning strategies, policymakers’ decisions, and considerable scientific contribution.